E-054 Pulserider-assisted treatment of intracranial aneurysms in the sterling registry. (23rd July 2022) - De Leacy, R; Puri, A; Starke, R; Jankowitz, B; Yoo, A; Gariel, F; Jahshan, S; Kulcsar, Z; Schirmer, C; Chivot, C; Howington, J; Pero, G; et al.
Abstract : Introduction: PulseRider (Cerenovus, Irvine, CA) is an adjunctive neck bridging device designed to aid in coiling of wide neck bifurcation intracranial aneurysms. We present outcomes of PulseRider assisted coil embolization of brain aneurysms in routine clinical practice included in the STERLING registry. Materials and Methods: STERLING (NCT03642639 ) is a prospective, global registry of endovascular treatment of intracranial aneurysms with Galaxy and MicrusFrame coils (Cerenovus, Irvine, CA). PulseRider cases from STERLING were included in this interim analysis. Primary outcome measures were core-lab assessed modified Raymond-Roy (mRR) occlusion at final procedural angiogram, and where available, at 6 months (+/-3 months) or 1 year (COVID allowed window: -3 months/+1.5 years). Safety outcomes were procedure- and device-related adverse events. Results: Seventeen subjects (mean age 64.4 ± 8.69 years, 12 female) were treated with the PulseRider device. All cases were unruptured and two were retreatments of previously coiled aneurysms. All aneurysms had saccular morphology, 14/15 (93.3%) were wide neck and 13/15 (86.7%) were at a bifurcation. Target aneurysm locations included basilar artery (6/15, 40.0%), MCA bifurcation (4/15, 26.7%), ACA (3/15, 20%), ICA terminus (1/15, 6.7%), and M2 (distal to bifurcation, 1/15, 6.7%), with a mean parent vessel diameter of 2.65 ± 0.440mm. PulseRider was successfully implanted with the ability to retain the coil mass in all cases. Mean packing density was 29.7 ± 11.32%. Adequate occlusion (mRR I or II) was achieved in 86.7% (13/15) cases immediately post procedure, 100% (3/3) at 6 moths, and 75% (3/4) at 1 year. There were no intraprocedural ruptures, no symptomatic thromboembolic events, and no device related SAEs through the maximum follow up. 87.5% (7/8) subjects had mRS 0–2 at 1 year. There were no aneurysm retreatments. Conclusion: In this interim analysis of the ongoing STERLING registry, treatment of intracranial aneurysms with the PulseRider device in conjunction with embolization using Galaxy and MicrusFrame coils showed excellent safety outcomes and high rates of adequate occlusion and good clinical outcome. Disclosures: R. De Leacy: 2; C; Imperative Care, Stryker Neurovascular, Cerenovus, Penumbra. 4; C; Synchron, Endostream, Q'Apel, Spartan Micro, Vastrax. A. Puri: 1; C; Medtronic Neurovascular, Stryker Neurovascular, Cerenovus, NIH. 2; C; Medtronic Neurovascular, Stryker Neurovascular, Cerenovus, Microvention, Agile Medical, Merit Medical, Corindus, Q'Apel, Arsenal Medical, Imperative Care, Perfuze Medical. 4; C; InNeuroCo Inc, Galaxy Therapeutics, Agile Medical, Perfuze Medical, NTI. R. Starke: 1; C; NREF, Joe Niekro Foundation, Brain Aneurysm Foundation, Bee Foundation, NIH, Medtronic. 2; C; Medtronic, Penumbra, Abbott, InNeuroCo, Cerenovus. 6; C; Medtronic, Penumbra, Abbott, InNeuroCo, Cerenovus. B. Jankowitz: 2; C; Stryker, Medtronic. 6; C; Medtronic. A. Yoo: 1; C; Medtronic, Cerenovus, Penumbra, Stryker. 2; C; Penumbra, Cerenovus. 4; C; Insera Therapeutics. F. Gariel: 2; C; Qynapse. S. Jahshan: None. Z. Kulcsar: None. C. Schirmer: 1; C; Penumbra. 4; C; Neurotechnology Investors. C. Chivot: None. J. Howington: 6; C; Chemence Medical. G. Pero: None. T. Yao: 2; C; Medtronic. 6; C; Medtronic, Microvention. A. Polifka: 2; C; Depuy Synthes. A. Evans: None. O. Zaidat: 1; C; Stryker, Medtronic, Cerenovus, Penumbra, Genentech, NIH. 2; C; Cerenovus, Stryker, Penumbra, Medtronic, Neuravi, NIH StrokeNet, Codman. 3; C; Ceronovus, Stryker, Penumbra, Medtronic. 4; C; Galaxy Therapeutics LLC. 6; C; Codman, Stryker, Penumbra, Medtronic Neurovascular.